Mechanical thrombectomy for mild stroke with anterior circulation large vessel occlusion: a multicenter cohort study - Zhang, Gaopan; Zhang, Neng; Li, Jingfan; Zhang, Siyu; Li, Manhe; Zhao, Xiongfei (Frontiers in Neurology, 2025)
BackgroundThe clinical benefit of mechanical thrombectomy (MT) for anterior circulation emergency large vessel occlusion (ELVO) in patients presenting with a mild National Institutes of Health Stroke Scale score (<6) remains uncertain. We aimed to assess the efficacy and safety of MT in this patient population.MethodsWe enrolled individuals presenting with mild stroke attributable to anterior circulation LVO from three stroke centers between March 2020 and June 2024. The primary endpoint was an excellent 90-day outcome, defined as a modified Rankin Scale (mRS) score of 0–1. Functional independence at day 90 (mRS 0–2) was considered the secondary endpoint. Safety endpoints consisted of symptomatic intracranial hemorrhage (sICH) and all-cause mortality within 90 days. Multivariable logistic regression with inverse probability of treatment weighting (IPTW) was applied to examine the association between MT and clinical outcomes.ResultsIn total, 140 individuals with mELVO were selected for analysis, receiving either MT [n = 48; 35 males; mean age: 59.9 years; NIHSS median: 4 (IQR 2–5)] or medical management (MM) [n = 92; 62 males; mean age: 61.9 years; NIHSS median: 3 (IQR 1–4)]. No statistically significant differences were observed between the MT and MM groups in excellent outcome (aOR = 0.93; 95% CI, 0.41–2.11), functional independence (aOR = 2.14; 95% CI, 0.77–5.91), symptomatic intracranial hemorrhage (aOR = 1.63; 95% CI, 0.37–7.14), or mortality (aOR = 0.56; 95% CI, 0.02–20.94). The results remained consistent after IPTW adjustment.ConclusionAmong patients with mELVO, MT was not associated with significantly different outcomes compared to MM. Further investigation through randomized controlled trials is warranted.